Preparedness needs of German municipal public health authorities - Raoul Maximilian Hecker; Jana Juenger; Peter Tinnemann (Human Biology and Public Health, 2026)
Background Recent crises have shown how complex threats to population health have become. Disease outbreaks, climate-related disasters, geopolitical tensions and disruptions to critical infrastructure do not occur in isolation: they overlap and reinforce one another, straining existing preparedness systems. In Germany, municipal public health authorities (“Gesundheitsämter”) are central to crisis response, yet their operational preparedness requirements are not clearly defined. Objectives We aimed to identify cross-cutting preparedness needs of German municipal public health authorities based on expert contributions presented at the 2025 DGÖGB symposium on Population Health Preparedness for Crisis (“Bevölkerungsmedizinische Vorbereitungen auf die Krise”). Sample and Methods We qualitatively analysed submissions from eight of the nine symposium speakers, extracting each contribution's main argument, thematic focus, and operational recommendations, checking AI-assisted summaries against the original documents and grouping recurring themes relevant to German municipal public health authorities. A post hoc step mapped the emergent domains onto the 2026 WHO/IANPHI framework. Results We identified five cross-cutting domains: governance and health security; institutional coordination and a common operating picture; critical infrastructure and digital resilience; workforce capacity and operational readiness; and continuity of essential health services and protection of vulnerable populations. Mapping showed the strongest alignment for legal authority, coordination, emergency management, workforce development, public health and social measures, and clinical care guidance. Conclusions Population health crisis preparedness requires a systemic approach integrating public health, civil protection, healthcare delivery, and critical infrastructure resilience, all domains involving municipal public health authorities. Strengthening their institutional capacity should therefore be central to German health security policy.